The Apollo 13 mission - Lemke, Donald B. (Graphic library. Disasters in history., 2006)
A graphic novel account of the "Apollo 13" near-disaster in graphic novel format, describing the treacherous journey home of three American astronauts after an explosion aboard their spacecraft.